1994
DOI: 10.1210/jcem.79.5.7962340
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inhibin/activin system messenger ribonucleic acids and proteins in ovarian follicles from women with polycystic ovarian syndrome.

Abstract: The role of inhibin, activin, and follistatin in the pathophysiology of polycystic ovary syndrome (PCOS) was investigated by examining the expression of human inhibin/activin subunit, follistatin, and type II activin receptor (ActRII and -IIB) messenger ribonucleic acid (mRNA) signals (via in situ hybridization) and encoded proteins (via immunocytochemistry) in ovarian follicles (n = 42) from 6 women diagnosed with PCOS. The localization patterns in cellular compartments were compared to those in small antral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Furthermore, premature sensitivity of granulosa cells from small antral follicles to LH has been reported in PCOS [31], thus LH might also stimulate inhibin B production directly in granulosa cells. In contrast to these findings and theories, several studies demonstrated reduced expression of the α-subunit in PCOS granulosa cells, which, possibly regulated by elevated LH levels, might be responsible for decreased inhibin A and B concentrations in follicular fluid [32,33]. Furthermore, an acute stimulatory effect of LH could not be mimicked by administrating a single dose of hCG to PCOS patients [16].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, premature sensitivity of granulosa cells from small antral follicles to LH has been reported in PCOS [31], thus LH might also stimulate inhibin B production directly in granulosa cells. In contrast to these findings and theories, several studies demonstrated reduced expression of the α-subunit in PCOS granulosa cells, which, possibly regulated by elevated LH levels, might be responsible for decreased inhibin A and B concentrations in follicular fluid [32,33]. Furthermore, an acute stimulatory effect of LH could not be mimicked by administrating a single dose of hCG to PCOS patients [16].…”
Section: Discussionmentioning
confidence: 82%
“…However, a few girls did have detectable levels of inhibin A and/or B (40). During the normal menstrual cycle, inhibin B concentrations increase in the early follicular phase in response to the rising FSH concentration exerting negative feedback on the pituitary (41,42), and it is primarily produced by the granulosa cells of the small developing follicles (43). The inhibin A concentration increases prior to ovulation, increases further after ovulation, and reaches peak values in the mid-luteal phase, primarily being produced by the granulosa cells of the dominant follicle and the corpus luteum (41,44 (47).…”
Section: Morphologymentioning
confidence: 99%
“…Such a conclusion was not unexpected in view of in vitro studies showing that inhibin enhanced both insulin-and LH-stimulated A production in cultured human TC (22,23). It has been previously proposed that abnormalities of the activin/inhibin paracrine or autocrine system may be involved in the hyperandrogenism of PCOS (45,48). Surprisingly, insulin appeared to not have a role in our theoretical multiple regression analysis model.…”
Section: Discussionmentioning
confidence: 47%
“…Jaatinen et al (44) and Roberts et al (45) effectively demonstrated in vitro, using in situ hybridization, that both GC and TC of normal and polycystic ovaries express inhibin subunit messenger ribonucleic acid. Moreover, ␣-subunit messenger ribonucleic acid levels were higher in TC compared to GC of polycystic ovaries, in contrast to the normal ovary (45,46). Accordingly, the serum levels of inhibin B in PCOS patients were significantly and positively correlated to the LH level in a recent study (47).…”
Section: Discussionmentioning
confidence: 89%